2013
DOI: 10.1093/cercor/bht059
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Covert Face Processing: fMRI Evidence from a Prosopagnosic Patient

Abstract: Brains can perceive or recognize a face even though we are subjectively unaware of the existence of that face. However, the exact neural correlates of such covert face processing remain unknown. Here, we compared the fMRI activities between a prosopagnosic patient and normal controls when they saw famous and unfamiliar faces. When compared with objects, the patient showed greater activation to famous faces in the fusiform face area (FFA) though he could not overtly recognize those faces. In contrast, the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…The peak activation observed in the DLPFC (BA9) at *224 msec was close in accord with an electrophysiological study that reported activation of the DLPFC at *170-210 msec (Adhikari et al, 2014); however, it was in a somatosensory domain. Activation of the DLPFC in decision-making has been repeatedly reported in previous fMRI and EEG studies (Adhikari et al, 2014;Heekeren et al, 2004Heekeren et al, , 2006Heekeren et al, , 2008Liu et al, 2013;Philiastides and Sajda, 2007). Our findings thus resolved a systematic sourcelevel activation pattern of temporal evolution in the FFA, PPA, and DLPFC for visual face or house categorization.…”
Section: Figsupporting
confidence: 83%
“…The peak activation observed in the DLPFC (BA9) at *224 msec was close in accord with an electrophysiological study that reported activation of the DLPFC at *170-210 msec (Adhikari et al, 2014); however, it was in a somatosensory domain. Activation of the DLPFC in decision-making has been repeatedly reported in previous fMRI and EEG studies (Adhikari et al, 2014;Heekeren et al, 2004Heekeren et al, , 2006Heekeren et al, , 2008Liu et al, 2013;Philiastides and Sajda, 2007). Our findings thus resolved a systematic sourcelevel activation pattern of temporal evolution in the FFA, PPA, and DLPFC for visual face or house categorization.…”
Section: Figsupporting
confidence: 83%
“…Facial expressions activate regions that have also been associated with unconscious or covert face and facial expression perception in normal subjects. These include ventral medio-frontal areas (Liu et al, 2013), PMC (Balconi & Bortolotti, 2013), precuneus (Pantazatos, Talati, Pavlidis, & Hirsch, 2012), SMG (Pantazatos et al, 2012) and cerebellum (Van den Stock, Vandenbulcke, Zhu, Hadjikhani, & . Remarkably, category-specific face processing areas along the ventral stream, such as the FFA or the OFA, were not activated in this contrast.…”
Section: Visual Perceptionmentioning
confidence: 99%
“…Finally, because the FFA has been demonstrated to be involved in the process of recognizing familiar and unfamiliar faces [44][45][46][47] , we examined whether there is a difference in modulation of the COMT genotypic profile between old (familiar) face recognition and new (relatively unfamiliar) face recognition. To control the effect of response bias on the accuracy 48 , we calculated the response bias [c = −Z(hit rate) + Z(false alarm…”
Section: Haplotype Analysismentioning
confidence: 99%